Multi-scale modeling of structural concrete [ - Maekawa, Koichi , 1938-; Ishida, Tetsuya; Kishi,Toshiharu , 1955- (Taylor & Francis, 2009)
"This book draws on the fields of materials and structural mechanics in an integrated way to address the questions of management and maintenance. It proposes a realistic way of simulating both constituent materials and structural responses under external loading and under ambient conditions. Where the research literature discusses component or element technology related to performance assessment, this book uniquely covers the subject at the level of the whole system including soil foundation, showing engineers how to model changes in concrete structures over time and how to use this for decision making in infrastructure maintenance and asset management."--BOOK JACKET